PERAN BANK INDONESIA DALAM MENGEMBANGKAN USAHA KECIL DAN MENENGAH DI WILAYAH EKS KARISIDENAN KEDIRI - Dina, Nur (Universitas Pawyatan Daha, 2022)
This study aims to determine the role played by Bank Indonesia in supporting the development of MSMEs in accessing financing in banking, providing banking information about potential MSMEs regarding their business feasibility. This research method includes field research. The method used in this research is descriptive qualitative method. By using interview techniques, observation and documentation. Interviews were used to collect data, observations were used to observe the role of Bank Indonesia in supporting MSME development of documentation to track data such as institutional documents. Based on the results of the study, it shows that the role of Bank Indonesia in developing MSMEs in the Kediri Residency area in the development of MSMEs in general is to increase income and employment so that it is very supportive and has a strategic role in realizing equal distribution of development results and maintaining economic stability through maintaining food commodity inflation.